The Effects of Adult Aging and Culture on Theory of Mind - Yong, Min Hooi *; Lawrie, Louisa; Schaefer, Alexandre; Phillips, Louise H. (Oxford University Press, 2022)
Objectives: Older adults tend to have poorer Theory of Mind (ToM) than their younger counterparts, and this has been shown in both Western and Asian cultures. We examined the role of working memory (WM) in age differences in ToM, and whether this was moderated by education and culture (the United Kingdom vs. Malaysia).